Kuis Kahoot Media Interaktif dalam Mengetahui Peningkatan Pemahaman Materi Metode Numerik Fisika Oseanografi Berbasis Pemograman Mathlab - Muhammad Fikry Syach (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2021)
This study aims to improve the practical understanding of the numerical method of oceanographic physics based on Mathlab software to calculate the roots of the Airy wave equation through the Kahoot application as an interactive media. This study used a population of 3 classes totaling 105 people. The determination of the increase in quiz scores with and without the Kahoot application was analyzed using the basic statistical comparison method, Independent T-Test Comparison (Intecomp) testing, as well as analysis of the distribution of the increase in quiz scores per class and per, mean predicate with a weighted scale of 4. The average score of the quiz scores without Kahoot 76.28; with Kahoot 84.96; the Intecomp P-Value test results 6,1.10-6 (α = 0.05), a significant increase in quiz scores from the use of the Kahoot application. The distribution of data for the increase in weighted quiz scores is 9.63%; As for the distribution of the rise in the average quiz score per class was 5.42%. Based on the statistical analysis test, it can be concluded that the use of the Kahoot application as an interactive media can increase the practitioner's understanding of the mathematical physics numerical method of oceanography based on Matlab.